OPTIMALISASI PENDEKATAN SAINTIFIK DENGAN PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI MADRASAH IBTIDAIYAH - Widya Pratiwi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The purpose of this article is to illustrate an inquari-learning strategy nowadays. Providing an in-depth illustrations, this ar-ticle written based on the teoretical study of Inquari Educational Technology as a learning strategy that focus on the process to search and discover. Material of the study should not give directly to students. Their roles in this learning to look for and discover the material by theirselves. By looking at the basic conception of Educational Technology and the current employment development, there will still be many new variation of learning will appear that is student-centered Approach. As a strategy, this learning have to develope students’ sistematical, logical, and critical thinking ability. Therefore, it needed a proper learning strategy to be implemented in islamic school (Madrasah Ibtidaiyah). Keywords : Pembelajaran inkuiri, Pendekatan siswa aktif, Madrasah Ibtidaiyah.